Estudo da eficiência de sistemas microemulsionados na remoção de contaminantes de água produzida - Nascimento, Yasmine Isis Fernandes do (2018)
Produced water is a byproduct of the oil extraction process and its composition vary according to the well, producing several contaminants that require a very complex treatment process. Thus, this water has been the object of study it can’t be disposed without the proper treatment. This work aimed to evaluate the since and use of microemulsion systems on the removal of produced water contaminants. A study of pseudternary diagrams, containing in the waters compositions: produced water enriched with metals (PWD) as aqueous phase (AP), hexane and kerosene as organic phase (OP), ratio co-surfactant/surfactant (C/S = 1 and 4), using six types of surfactants: Renex, Alkonat, coconut oil saponified (SCO), sodium dodecyl sulfate (SDS), cetiltrimethylammonium bromide (CTAB) and ultramina; and as co-surfactant n-butanol. After the diagrams development and choice of the best system, the process of extraction of contaminants that was contained in the PWD, was performed choosing three points located in the Winsor II region, in an area rich in water and contains a low amount of surfactant, the compositions were denominated as maximum point (30% C/S, 10% OP, 60% AP); medium point (17.5% C/S), 7.5% OP, 75% AP); minimum point (5% C/S), 5% OP, 90% AP). For the determination of the contaminants concentration (metals, anions and PAHs) different analysis methods were used, including ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry), HPLC-FLD (High Performance Liquid Chromatography with Fluorescent Detector) and X-Ray Fluorescent. The system that obtained the higher removal efficiency was the one containing SCO as surfactant, C/S ratio = 4 and hexane as oily phase. The best result of contaminants removal was associated with the medium point which composition was (17.5% C/S, 7.5% OP, 75% AP). Therefore this study has shown that the use of microemulsion systems may be an alternative for the correct management wastewater generated by the petroleum industry.